Implementasi Pelayanan Identitas Kependudukan Digital di Dinas Kependudukan dan Pencatatan Sipil Kota Surabaya - Syafa Armia Zafira; Oktarizka Reviandani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Surabaya is the city with the second largest population in Indonesia and continues to experience an increase in population. This increase is related to the problem of fulfilling rights, interests, protection and public services. One of them is the acquisition of the right to identity which is part of civil rights and freedoms. This is the responsibility and commitment of the Surabaya City Population and Civil Registration Office to provide Digital Population Identity (IKD) services to the community. This research aims to know and understand the Implementation of Digital Population Identity (IKD) Services at the Surabaya City Population and Civil Registration Office. This research method uses qualitative methods with data collection techniques of interviews, observation and documentation. The theory used is the theory of policy implementation by Edward III (1980) quoted from Anggara (2018), including communication, resources, disposition and bureaucratic structure. The results of this study show that the implementation of Digital Population Identity (IKD) services at the Surabaya City Population and Civil Registration Office has been carried out well, but there are shortcomings with many people who do not know the use of Digital Population Identity (IKD) as a companion to KTP-el.